2022
DOI: 10.1039/d2tc00976e
|View full text |Cite
|
Sign up to set email alerts
|

Getting closer to the intrinsic properties of Ni2+salen polymer semiconductors accessed by chain isolation inside silica nanochannels

Abstract: The scientific problem aimed to be solved by our research consists in the energy transport improvement in Ni2+salen polymer semiconductors by isolation of individual chains inside mesoporous silica channels capable...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Whereas the first cathodic peak at ∼1.00 V (Figure a) and ∼0.95 V (Figure b) and the second cathodic peak at ∼0.70 V (Figure a) and ∼0.65 V (Figure b) corresponded to the bisphenolic cation reduction to bisphenolic cation radicals and the consequent bisphenolic cation radical reduction to the neutral forms, respectively. After the first cycle of PD polymerization, the polymer film started to grow, which was evident from the appearance of broad anodic and cathodic waves growing in the subsequent cycles (characteristic of initial electrochemical doping and generation of charge transport speciesbisphenolic radical cations inside the conducting polymer layer already deposited on the electrode), ,, both centered between 0.50 and 0.85 V for poly­(NiSaltMe)-PD low′ (Figure a) and poly­(NiSaltMe)-PD high′ (Figure b). The charges passed during all PD polymerizations are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the first cathodic peak at ∼1.00 V (Figure a) and ∼0.95 V (Figure b) and the second cathodic peak at ∼0.70 V (Figure a) and ∼0.65 V (Figure b) corresponded to the bisphenolic cation reduction to bisphenolic cation radicals and the consequent bisphenolic cation radical reduction to the neutral forms, respectively. After the first cycle of PD polymerization, the polymer film started to grow, which was evident from the appearance of broad anodic and cathodic waves growing in the subsequent cycles (characteristic of initial electrochemical doping and generation of charge transport speciesbisphenolic radical cations inside the conducting polymer layer already deposited on the electrode), ,, both centered between 0.50 and 0.85 V for poly­(NiSaltMe)-PD low′ (Figure a) and poly­(NiSaltMe)-PD high′ (Figure b). The charges passed during all PD polymerizations are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The group of poly­(NiSalen)­s is assigned to polymer semiconductors that reveal a mixed redox and π-conjugated conductivity in a moderately electron-donating medium. , Their Faradaic charge conduction mechanism can be explained in a simplified way as the transport of delocalized valence electrons within the model of a Peierls distorted polymer lattice, such as that for polyphenylene-type polymers . Importantly, this charge transport occurs only in a particular continuous range of potentials involving oxidized polymer forms (bisphenolic radicals and bisphenolic cations), revealing the p-type of electrochemical doping, where no metal-centered oxidation, such as Ni 2+ /Ni 3+ , is observed. In a moderately electron-donating medium, poly­(NiSalen) behaves like a polyphenylene, with the Ni 2+ ion acting as a bridge between biphenylene moieties …”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical properties of the electrode materials were evaluated with different scan rates at a potential window ranging from +0.15 to +1.0 V. The performed CV study of CP-1, CuO NPs, and CuO@CP-1 revealed that CP-1 followed the pseudo-capacitive behavior. 17,81 CP-1 has shown a better rectangular CV curve with a large area, which appeared due to the electrochemical double-layered capacitor behavior of CP-1. The observance of a redox peak in the CP-1 was attributed to the capacitive feature, followed by a reversible faradaic reaction.…”
Section: Energy Storage Studies Of Modified Cp-1-gce Cuo-gce and Comp...mentioning
confidence: 97%